RECONCEPTUALIZING “GOOD LITERATURE” IN EFL EDUCATION: CRITERIA AND TEACHER COMPETENCIES FROM LECTURERS’ PERSPECTIVES - Adhim, Syarif; Setiawan, Rahmat (Universitas Jambi, 2026)
This research aims to explore literature lecturers’ perspectives on the criteria of literary works that are appropriate for use in English as a Foreign Language (EFL) classroom and the competencies required of teachers to effectively integrate literature into the teaching and learning process. This study is grounded in the theories of literature integration in language learning, literary literacy, and a humanistic pedagogical approach that emphasizes cultural values, critical reflection, and character development through literary texts. This research employed a qualitative design with a descriptive-interpretative approach. The data were collected through semi-structured interviews with two expert lecturers from the Faculty of Literature who specialize in literary studies and have extensive experience in teaching literature. The data were then analysed using thematic analysis to identify patterns of meaning and major themes. The findings reveal two main results. First, literary works considered pedagogically appropriate fulfill three essential aspects: cultural enrichment, civilisation conformity, and pedagogical adaptability. Second, the effectiveness of using literature largely depends on teachers’ competencies, including literary literacy, contextual knowledge enrichment, a humanistic approach, as well as public speaking and storytelling skills. This study concludes that literature can function as a contextual, reflective, and meaningful medium for language learning when mediated by teachers who possess adequate literary and pedagogical competencies.